Development of Flappy Chem Game Media on Electron Configuration Materials on Students’ Happiness Level - Shabrina Nabilah; Achmad Lutfi (Yayasan Keluarga Guru Mandiri, 2022)
This study aims to produce the Flappy Chem game as a learning media on electron configuration material referring to the feasibility indicators, namely the validity, practicality, and effectiveness of the developed game media. This study uses a 4D development model. The instrument used is a validation sheet, student response questionnaire sheet, student happiness level questionnaire sheet, pretest, and posttest. The limited trial was conducted at SMA Negeri 3 Sidoarjo with a total of 30 students. The results of the validity test got a score of more than 3 with good categories. Practicality scores get an average percentage of 85% for each goal with a very practical category. The effectiveness score can be seen through the learning outcomes of students and the level of happiness. Classical completeness achieved is 87% and the level of happiness of students is 83% with a very effective category. Based on this explanation, it can be concluded that the Flappy Chem game media has met the feasibility indicators, namely validity, practicality, and effectiveness so that it can be used as a game-based learning media.